Angle-dependent lubricated tribological properties of stainless steel by femtosecond laser surface texturing. (July 2016) - Wang, Zhuo; Li, Yang-Bo; Bai, Feng; Wang, Cheng-Wei; Zhao, Quan-Zhong
Abstract: Lubricated tribological properties of stainless steel were investigated by femtosecond laser surface texturing. Regular-arranged micro-grooved textures with different spacing and micro-groove inclination angles (between micro-groove path and sliding direction) were produced on AISI 304L steel surfaces by an 800 nm femtosecond laser. The spacing of micro-groove was varied from 25 to 300 μm, and the inclination angles of micro-groove were measured as 90° and 45°. The tribological properties of the smooth and textured surfaces with micro-grooves were investigated by reciprocating ball-on-flat tests against Al2 O3 ceramic balls under starved oil lubricated conditions. Results showed that the spacing of micro-grooves significantly affected the tribological property. With the increase of micro-groove spacing, the average friction coefficients and wear rates of textured surfaces initially decreased then increased. The tribological performance also depended on the inclination angles of micro-grooves. Among the investigated patterns, the micro-grooves perpendicular to the sliding direction exhibited the lowest average friction coefficient and wear rate to a certain extent. Femtosecond laser-induced surface texturing may remarkably improve friction and wear properties if the micro-grooves were properly distributed. Highlights: Angle-dependent lubricated tribological properties of stainless steel were studied. Micro-grooved textures had a marked potential for improving tribological property. Effects of micro-groove inclination angles on tribological properties were studied.